Tilapia Swimming Velocity Study Using Computer Vision Technique - Jongjaraunsuk , Roongparit; Taparhudee, Wara (Burapha Science Journal, 2026)
This study was divided into 2 experiments: 1) the effect of different numbers of frames per second on the received data, and 2) the effect of different formalin concentrations on tilapia swimming velocity. Three fish, each weighing between 0.5 and 1 g were used for each experiment (3 replicates). The first experiment applied four frame rates of 1, 3, 5 and 10 frames per second (FPS) to determine fish swimming velocity (FSV). Results showed no significant differences among treatments (P > 0.05). The swimming velocity set (V-set) and number of frames obtained for use at one processing speed (Frame/V-set) using 1 FPS and 3 FPS were not statistically different (P > 0.05). Hence, the 3 FPS rate was chosen for the second experiment and three levels of formalin concentrations were applied at 0, 300 and 600 mg/L to compare FSV differences. Results showed that average FSV in the three trials were statistically different (P < 0.05). Average FSV of the first treatment (no formalin applied) was highest at 0.038 ± 0.005 m/s, the second treatment (300 mg/L of formalin (37% formaldehyde, Sigma-Aldrich ®) was 0.029 ± 0.025 m/s, and not significantly different (P > 0.05) from the FSV results of the first and third treatment (600 mg/L) and the third treatment was 0.019±0.015 m/s, that less than the first treatment but not significantly different (P > 0.05) with the second treatment respectively. The results of this study show that the computer vision techniques can be applied to study behavior of other aquatic animals. The advantages are obtaining accurate result and can continuously monitor without disturbing the aquatic animals.